(untitled) (Global Journal of Human-Social Science, 2018)
Flood is a natural disaster that affects lives livelihoods household food security and natural ecosystems Hence the study sought to determine flood effects on agricultural productivity Implications for Mangrove Forest Ecosystem in Akpabuyo Cross River State Nigeria Specifically the paper identified high and low-risks flood areas in Akpabuyo determined the frequency of flood events and extent of agricultural land inundation identifying the crops species affected by flooding and assessed the income and food survival strategies of farmers affected by annual flood events Descriptive statistics frequency counts percentages and averages were employed to analyze the data derived from a structured questionnaire and field measurement of elevation of high and low-risk flood areas Results revealed that the agricultural land at high risk of flooding is those with 1-44 metres elevation above sea level Table 1 Findings on Table 4show that the food staple most affected are the root or tuber species with 77 52 percent annual destruction vegetable species were also at high risk and some economic crops like Musa spp plantain were also at high risks of destruction The result further revealed that income loss and food shortages occasioned from flooding of agricultural land are mitigated by Mangrove Forest Ecosystem Resources Extraction Table 6 Thus conservation of the Mangrove Forest ecosystem in Akpabuyo and Cross River State is tied to the efficient management and mitigation of flood events in agricultural land